Mutations in the interleukin receptor IL11RA cause autosomal recessive Crouzon‐like craniosynostosis. Issue 4 (19th August 2013) - Keupp, Katharina; Li, Yun; Vargel, Ibrahim; Hoischen, Alexander; Richardson, Rebecca; Neveling, Kornelia; Alanay, Yasemin; Uz, Elif; Elcioğlu, Nursel; Rachwalski, Martin; Kamaci, Soner; Tunçbilek, Gökhan; et al.
Abstract We have characterized a novel autosomal recessive Crouzon‐like craniosynostosis syndrome in a 12‐affected member family from Antakya, Turkey, the presenting features of which include: multiple suture synostosis, midface hypoplasia, variable degree of exophthalmos, relative prognathism, a beaked nose, and conductive hearing loss. Homozygosity mapping followed by targeted next‐generation sequencing identified a c.479+6T>G mutation in the interleukin 11 receptor alpha gene (IL11RA) on chromosome 9p21. This donor splice‐site mutation leads to a high percentage of aberrant IL11RA mRNA transcripts in an affected individual and altered mRNA splicing determined by in vitro exon trapping. An extended IL11RA mutation screen was performed in a cohort of 79 patients with an initial clinical diagnosis of Crouzon syndrome, pansynostosis, or unclassified syndromic craniosynostosis. We identified mutations segregating with the disease in five families: a German patient of Turkish origin and a Turkish family with three affected sibs all of whom were homozygous for the previously identified IL11RA c.479+6T>G mutation; a family with pansynostosis with compound heterozygous missense mutations, p.Pro200Thr and p.Arg237Pro; and two further Turkish families with Crouzon‐like syndrome carrying the homozygous nonsense mutations p.Tyr232* and p.Arg292*. Using transient coexpression in HEK293T and COS7 cells, we demonstrated dramatically reduced IL11‐mediated STAT3 phosphorylation for all mutations. Immunofluorescence analysis of mouse Il11ra demonstrated specific protein expression in cranial mesenchyme which was localized around the coronal suture tips and in the lambdoidal suture. In situ hybridization analysis of adult zebrafish also detected zfil11ra expression in the coronal suture between the overlapping frontal and parietal plates. This study demonstrates that mutations in the IL11RA gene cause an autosomal recessive Crouzon‐like craniosynostosis.